Bamboo as a Raw Material for Pulp and Paper - Singh, S. P.; Naithani, Sanjay (Indian Forester, 2008)
Bamboo contributes as a source of long fiber in the pulp and paper furnish. The physical and chemical characteristic of bamboo as a raw material varied form species to species. The raw material having low lignin content reduces chemical consumption and pollution load during pulping and bleaching whereas high holocellulose content results in more productivity. Anatomical characters like fibre morphology is one of the important character which plays very important role on the structure and properties of the end products like paper and textile. The ratio of length and wall thickness affect the flexibility and collapsibility of fiber, which inturn reduces the energy requirement during beating. There is need to fill up the gap between demand and supply by raising quality bamboo.